Exogenous Hydrogen Sulfide Activates PI3K/Akt/eNOS Pathway to Improve Replicative Senescence in Human Umbilical Vein Endothelial Cells - Haiming Niu; Jianwei Li; Hongkai Liang; Guishen Wu; Miaolian Chen (Cardiology Research and Practice)
Background. Endothelial cell senescence is one of the key mechanistic factors in the pathogenesis of atherosclerosis. In terms of molecules, the phosphatidylinositol 3-kinase/protein kinase B/endothelial nitric oxide synthase (PI3K/Akt/eNOS) signaling plays an important role in the prevention and control of endothelial cell senescence, while hydrogen sulfide (H2S) improves the induced precocious senescence of endothelial cells through the PI3K/Akt/eNOS pathway. Comparatively, replicative senescence in endothelial cells is more in line with the actual physiological changes of human aging. This study aims to investigate the mechanism by which H2S improves endothelial cell replicative senescence and the involvement of the PI3K/Akt/eNOS pathway. Methods. we established a model of replicative senescence in human umbilical vein endothelial cells (HUVECs) and explored the effect of 200 μmol/L sodium hydrosulfide (NaHS; a donor of H2S) on senescence, which was determined by cell morphology, the expression level of plasminogen activator inhibitor 1 (PAI-1), and the positive rate of senescence-associated β-galactosidase (SA-β-Gal) staining. Cell viability was detected by MTT assay to evaluate the effect of NaHS and the PI3K inhibitor, LY294002. Meanwhile, the protein expression of PI3K, Akt, p-Akt, and eNOS in endothelial cells of each group was detected by Western blot. Results. the replicative senescence model was established in HUVECs at the passage of 16 cumulative cell population doubling values (CPDL). Treatment with NaHS not only significantly reduced the expression of PAI-1 and the positive rate of SA-β-Gal in HUVEC’s replicative senescence model but also notably increased the expression of PI3K, p-Akt, p-eNOS, and the content of nitric oxide(NO). However, the effects of NaHS on the expression of the pathway and the content of NO in HUVECs were abolished when LY294002 specifically inhibited PI3K. Conclusion. NaHS improves the replicative senescence of HUVECs with the contribution of the PI3K/Akt/eNOS pathway.